2020
DOI: 10.3390/plants9060757
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Composition and Anti-Melanoma Activity of White Forsythia (Abeliophyllum distichum Nakai) Organ Extracts

Abstract: Abeliophyllum distichum Nakai, commonly called white forsythia, is a monotypic genus endemic to Korea. Although A. distichum is mainly used as an ornamental plant because of its horticultural value, recent studies have demonstrated its bioactivities, including antioxidant and anti-inflammatory activities, prompting us to investigate the potential anticancer effect of A. distichum organ extracts (leaves, fruit, and branches) against human melanoma SK-MEL-2 cells. The methanol extract of A. distichum leaves (AL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…This plant belongs to a monotypic genus (i.e., a genus with only a single species), which highlights the importance of this plant as a unique genetic resource [ 11 ]. Although this plant has been cultivated as an ornamental plant in Korea, because of its horticultural value, recent studies have reported that A. distichum possesses several therapeutic properties, including antioxidant, anti-inflammatory, anti-melanogenic, anti-cancer, and anti-diabetic effects [ 11 , 12 , 13 , 14 ]. Recently, it has been shown that A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This plant belongs to a monotypic genus (i.e., a genus with only a single species), which highlights the importance of this plant as a unique genetic resource [ 11 ]. Although this plant has been cultivated as an ornamental plant in Korea, because of its horticultural value, recent studies have reported that A. distichum possesses several therapeutic properties, including antioxidant, anti-inflammatory, anti-melanogenic, anti-cancer, and anti-diabetic effects [ 11 , 12 , 13 , 14 ]. Recently, it has been shown that A .…”
Section: Introductionmentioning
confidence: 99%
“…distichum [ 15 ]. Among phytochemicals in A. distichum , phenolic and phenylethanoid glycosides have been reported as multiple active compounds with therapeutic value [ 11 , 14 ]. For example, acteoside (phenylethanoid glycoside) and isoacteoside (dihydroxypheynylethyl glycoside) identified in leaves of A. distichum , exhibited antioxidant and anti-inflammatory activities, respectively [ 15 , 16 ], indicating that A. distichum could have functional applications in the cosmetic, biomedical, pharmaceutical, and other industries.…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenols may reduce certain age-associated diseases such as cancer and Alzheimer’s disease by mitigating increased cellular damage through the reduction of reactive oxygen species (ROS) by the down-regulation of antioxidant enzymes [ 2 , 3 ] and the modulation of the inflammatory status, autophagy function and gut microbiota [ 4 ]. The antiproliferative and cytotoxic effects of polyphenols on cancer cells are attributed to cell cycle arrest and the molecular regulation of specific genes [ 5 , 6 , 7 , 8 , 9 ]. Polyphenols may control microbes such as bacteria and fungi [ 10 , 11 ] and might be used as natural food preservatives [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…An unsolved question in this study is which compound(s) of LE exhibited anti-osteoclastogenic activity. Recent studies demonstrated that A. distichum methanol extract possesses more than 20 polyphenolic compounds [ 14 , 15 , 37 ]. Considered that seven compounds (acteoside, chlorogenic acid, caffeic acid, ferulic acid, naringenin, taxifolin, and quercetin) among the polyphenolic compounds are known to inhibit RANKL-mediated osteoclastogenesis [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], we assume that these bioactive compounds might play a role in anti-osteoclstogenesis.…”
Section: Discussionmentioning
confidence: 99%